Assessment of knowledge and attitude of radiographers towards radiation protection in al Qassim region, Saudi Arabia - Alotaibi, Layali; Alkhalifah, Bassam (International Journal of Medicine, 2019)
Background: Ionizing radiation is important medical imaging techniques. Medical imaging is a powerful tool for diagnosis of many diseases. Although, it has potential benefits and it has harmful risks that should not be ignored.Objective: This study aims to assessing the current knowledge and attitude toward radiation protection, radiological examination doses, and impact of radiation exposure among radiographers working in health facilities in Al-Qassim, Saudi Arabia.Design and Setting: This cross sectional prospective survey included 100 radiographers from different governmental and private hospitals in Al-Qassim, Saudi Arabia, in the duration from October 2018 to December 2018, through self –administered questionnaires The questionnaire consisted of three sections: the first section focused on radiographers’ demographic data, the second assessed the current knowledge and attitude towards radiation protection, and the third assessed the current knowledge and attitude towards radiological examination doses .Results: Out of the 100 responders to the survey, 69 male and 31 female radiographers were included. It was observed that most of the radiographers were younger than 30 years old, with less than five years of experience in 54% of them. Most of the responders (84%) had a bachelor degree or higher.The level of education and years of experience influenced the knowledge of radiation doses especially for abdominal/pelvis CT p=0.016), thyroid isotope scan (p<0.001) and brain MRI doses (p=0.002). Additionally, a significant difference was found in awareness to patient radiation protection measures (p<0.001) and the radiographers’ opinion on the personnel who are exposed to radiation the most (p<0.001).Conclusion: the current level of knowledge is inadequate. Training programs and on job training can improve the practice. Further studies with larger sample size are needed.